Introducing English vocabulary through the provision of tutoring to enhance students' vocabulary comprehension at Batang Arah Tapan Elementary School: Mengenalkan Kosakata Bahasa Inggris Melalui Pengadaan Bimbingan Belajar Dalam Meningkatkan Pemahaman Kosakata Siswa Di Sekolah Dasar Negeri Batang Arah Tapan - Suci Ramadhani; Ahmad Khairul Nuzuli; Winda Oktaviana (ASIAN: Indonesian Journal of Learning Development and Innovation, 2023)
This research aims to identify whether introducing English vocabulary through tutoring can enhance students' vocabulary comprehension. The research design employed is an experimental study. This study measures students' vocabulary comprehension before and after the intervention of introducing vocabulary through tutoring. The research was conducted at Batang Arah Tapan Elementary School, involving an experimental group receiving the intervention and a control group. The results of the research indicate that the learning process through tutoring in Nagari Batang Arah, Tapan, successfully created a positive and enthusiastic environment for students. Children showed enthusiasm in acquiring new knowledge, particularly in understanding English vocabulary that had not been previously taught in school. The hypothesis testing results show a significant difference in English vocabulary comprehension between the experimental and control groups. This suggests that introducing English vocabulary through tutoring effectively enhances students' vocabulary comprehension